Phenoxy-benzothiadiazole dyes: Synthesis, photophysical properties and preliminary application in OLEDs. Issue 31 (1st August 2018) - Pazini, Alessandra; Maqueira, Luis; Avila, Harold C.; Valente, Felipe M.; Aderne, Rian E.; Back, Davi; Aucélio, Ricardo Q.; Cremona, Marco; Limberger, Jones
Graphical abstract: Highlights: Phenoxy-BTD derivatives were synthesized for the first time. Novel fluorescent phenoxy-aryl-BTD derivatives were synthesized and characterized. The compounds are highly luminescent. A donor-BTD-donor phenoxy-BTD derivative was applied as emissive layer in a green OLED. Abstract: The synthesis of a phenoxy-benzothiadiazole (BTD) derivative is reported for the first time. This derivative was employed as an intermediate in the obtention of two novel highly fluorescent aryl-phenoxy-BTD dyes. Their photophysical properties were evaluated in solution and the results indicate a strong intramolecular charge transfer (ICT) character in the excited state. The luminophore3a, possessing a donor-BTD-phenoxide architecture, exhibits superior fluorescence quantum yield (0.67) than the designed acceptor-BTD-phenoxide dye (0.06). After electrochemical and photoluminescence characterization of thin films of3a, an OLED with the configuration ITO/PEDOT:PSS/3a /TPBi/LiF/Al was constructed. This device displayed a green emission centered at 547 nm, with CIE coordinates of (0.40, 0.55). For comparison, an OLED using a previously reported luminescent BTD-pyridyl derivative was also constructed. The OLED made with the phenoxy-BTD derivative operated using less current density and led to higher irradiance and electrical stability, indicating the high potential of ArO-BTD dyes for future application in electroluminescent devices.